Questions of the overall dependability of the scada system in the corporate infrastructure - Simeonova, Tsvetelina (Yearbook Telecommunications, 2021)
The paper considers the peculiarities of the SCADA (energy infrastructure management system in the railway infrastructure), as well as issues of the overall dependability in the corporate infrastructure, which is the aim of the study. The study, based on the accepted structure and values of the parameters, examines what depends on and how the readiness factor of a SCADA system changes when the recovery intensity changes and at a fixed failure rate. The results show that with increasing recovery intensity, the readiness factors of the telecommunications network and SCADA system thus defined increase, while reducing the downtime. For a more in-depth study of the overall reliability of the SCADA system, it is necessary to set specific normatively accepted dependability parameters of all connected elements, as well as a real set structure. Based on the fact that with backup resources provided, a defined dependability of the system can be ensured at preset values of the reliability parameters of its components and the backup structure; the opposite problem can also be solved. The proposed approach for studying the reliable behavior of the SCADA system within the corporate infrastructure can be noted as a contribution of the present work and conclusions are made for the practical use of the results.